Risk factors of metabolic dysfunction-associated fatty liver disease in Chinese nurses: an ambispective cohort study - Wang, Jing; Zhang, Heli; Zhang, Xiaotian; Wang, Jingpin; Chen, Hongbo; Li, Baohua (Frontiers in Public Health, 2025)
BackgroundMetabolic dysfunction-associated fatty liver disease (MAFLD) refer to fatty liver disease related to systemic metabolic dysregulation, which is closely related to unhealthy lifestyles such as staying up late and eating irregularly. MAFLD has become most prevalent chronic liver disease and become a high incidence disease among nurses. Health and good condition of nurses are the basis to ensure the safety and quality of life of patients. Little is known about the risk factors of MAFLD in nurses.MethodWe conducted an ambispective cohort study of the National Nurses' Health Study from 2018 to 2022 in a tertiary hospital in China. The data were collected by questionnaires and physical examination records. Analysis was done using SPSS 26.0. Risk factors for MAFLD were estimated by multivariable Cox proportional hazard regression using forward stepwise selection.ResultA total of 777 nurses were included in this study. The incidence of MAFLD in nurses exceeds the global average. Age at diagnosis (p = 0.011), BMI (p = 0.000), FBG (p = 0.048), TG (p = 0.009), uric acid (p = 0.011), female (p = 0.012), like eating oily food (p = 0.049) and spicy food (p = 0.028), and frequency of outgoing-food (p = 0.042) were risk factors for MAFLD.ConclusionThe incidence of MAFLD in nurses was higher than the global average and has become an occupational health concern. Age, BMI, female gender, fasting blood glucose (FBG), triglycerides (TG), uric acid, oily foods, spicy foods, and the frequency of eating out were risk factors for MAFLD occurrence. In the future, the focus should be on risk factors for MAFLD in nurses and developing intervention programs to improve nurse health and well being.